2021
DOI: 10.1039/d1ra01978c
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical insights into the electroreduction mechanism of N2 to NH3 from an improved Au(111)/H2O interface model

Abstract: The associative alternating and distal mechanisms may be able to parallelly occur. The initial N2 reduction into N2H species is rate determining step, which may be able to be regarded as the origin of high overpotential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…0.24 eV vs. 1.75 eV). 29 The comparison of activation barriers between HER and initial N 2 electroreduction well explains why Au electrocatalytic activity is unsatisfactory despite the relatively higher faradaic efficiency that can be experimentally achieved compared to other transition metals. 21,22,55 In this work, the barriers of HER are evaluated by MEP analysis at AuM(111)/H 2 O interfaces (M = Ni, Pd, Pt, Ru, and Ta) with different atomic ratios and compared with that of initial N 2 electroreduction into N 2 H species to quantify the challenge in designing high efficient Au-based alloy electrocatalysts.…”
Section: Competing Hydrogen Evolution Reactionmentioning
confidence: 91%
See 3 more Smart Citations
“…0.24 eV vs. 1.75 eV). 29 The comparison of activation barriers between HER and initial N 2 electroreduction well explains why Au electrocatalytic activity is unsatisfactory despite the relatively higher faradaic efficiency that can be experimentally achieved compared to other transition metals. 21,22,55 In this work, the barriers of HER are evaluated by MEP analysis at AuM(111)/H 2 O interfaces (M = Ni, Pd, Pt, Ru, and Ta) with different atomic ratios and compared with that of initial N 2 electroreduction into N 2 H species to quantify the challenge in designing high efficient Au-based alloy electrocatalysts.…”
Section: Competing Hydrogen Evolution Reactionmentioning
confidence: 91%
“…† Our most recent and previous theoretical studies have shown that the initial N 2 electroreduction into N 2 H intermediate is a rate-determination step during NH 3 production on Au and other late transition metals. 29,42,43 An extremely high activation barrier of ca. 1.75 eV for initial N 2 electroreduction into the N 2 H species was obtained on a pure Au(111) surface in our most recent study, 29 which may be able to be looked upon as the origin of unsatisfied faradaic efficiency and NH 3 yield during N 2 electroreduction on clean Au electrodes.…”
Section: N 2 Adsorption and Activation In The Gas Phasementioning
confidence: 99%
See 2 more Smart Citations
“…From a theoretical perspective, it remains debatable whether the N 2 adsorption and activation occur more favourably at the solid-liquid interface (i.e., dissolved N 2 as reactant) or at the three phase interface (i.e., gaseous N 2 as reactant). Ou et al 50 modelled a gold (111) surface flooded with H 2 O and found the electronic interaction between dissolved N 2 and H 2 O is critical in reducing the activation energy of the ratedetermining step (the first hydrogenation step to produce N 2 H). By contrast, when exposing Au only to N 2 gas without the involvement of H 2 O, destabilizing the NRN bond at the Au-N 2 interface suffers a higher kinetic barrier because of an insufficient valence electron gain from H 2 O.…”
Section: Reviewmentioning
confidence: 99%